Application of Philosophy of Science to the Development of Science - Muhammad Adhil Fatih Nasrullah; Maspuroh; Syifa Azzahra; Siti Maelah Hapid; Wina Lusina (Penerbit Hellow Pustaka, 2025)
This study focuses on explaining the application of how the philosophy of science plays a role in the development of science, especially in the development of Islamic religious science. By discussing the dynamics of scientific knowledge and the model of application of ontology and epistemology of science. The understanding and actions carried out by some Muslims do not reflect the universality and mercy of Islamic teachings. There are some Muslims who are very textual in understanding and practicing Islam, some are secular liberals. In fact, humans were created by Allah SWT with reason. Human thinking is born from human sensory factors towards the universe (physics), religious texts (metaphysics), and social relations (anthropology), as well as things related to the objects of human thought. These thoughts continue to develop according to the times. Like something that originated from a myth into a scientific study with the theories of scientists. Of course, to maintain the value of mercy and universality, the theory must be studied coherently, honestly and purely for a truth in order to maintain the values ​​of the purity of science itself. Philosophy has a role as a discussion of the reality of the journey towards a deep understanding of science. The journey towards a deep understanding of reality involves an understanding of the nature of science itself, how science is obtained, and how science describes reality. So that the philosophy of science plays a role in the formation of scientific concepts and theories, the development of scientific methods, and maintaining objectivity, accuracy, and reproducibility in scientific research. So by understanding and practicing this, Muslims can become a people who adhere to the nash (text), enthusiastically seek the benefits of all realities, and are responsive to all challenges/changes of the times. The author uses a qualitative approach, namely using a descriptive-analytical method from relevant sources.